Wender Utah Rating Scale-25 (WURS-25): psychometric properties and diagnostic accuracy of the Swedish translation. (2nd October 2018) - Kouros, Ioannis; Hörberg, Niklas; Ekselius, Lisa; Ramklint, Mia
Abstract: Objective: The aim of this study was to examine the psychometric properties and diagnostic accuracy of the Swedish version of the Wender Utah Rating Scale (WURS) in psychiatric patients with similar symptoms but diagnosed with either attention deficit hyperactivity disorder (ADHD), bipolar disorder (BP), and/or borderline personality disorder (BPD). Methods: A total of 121 patients from an outpatient psychiatric clinic for young adults (18–25 years) were diagnosed using the Structured Clinical Interview for DSM Axis I and Axis II (SCID-I and SCID-II), and ADHD was diagnosed using the Schedule for Affective Disorders and Schizophrenia for School-Age Children (K-SADS). WURS were filled in by the participants and compared with a diagnosis of ADHD according to K-SADS. Results: Internal consistency of the WURS was 0.94. The principal component analysis resulted in a three-factor solution that accounted for 61.3% of the variance. The ADHD group had significantly higher mean scores compared to all other groups. The diagnostic accuracy of the WURS was examined using AUC and ROC analysis, and the optimal cut-off score was 39, with a sensitivity of 0.88 and specificity of 0.70, with AUC 0.87, 95% CI 0.80–0.94, PPV 0.59, and NPV 0.92. Conclusion: The psychometric properties of the Swedish WURS were good. For assessment of adult ADHD, in patients with symptoms of emotional instability, impulsivity, and attention problems but of different origins, a somewhat higher cut-off score than the originally suggested was preferable for identification of ADHD.